Identifying and assessing subsidies and other incentives harmful to biodiversity A comparative review of existing national-level assessments and insights for good practice - Matthews, Alan (OECD Publishing, 2022)
Despite calls for the reform of incentives, including subsidies, harmful to biodiversity, including under the Convention on Biological Diversity and its 2011-2020 Aichi Targets, very few countries to date have undertaken what is considered the first step in this process, namely, to identify and assess the types and magnitudes of any incentives in place at the national level which are harmful for biodiversity or the environment more broadly. This paper begins with a brief literature review on subsidies harmful to biodiversity, followed by a detailed review and comparison of the existing national level studies to identify and assess subsidies and other incentives harmful to biodiversity or the environment. The report concludes with guidance and good practice insights to identify and assess subsidies and other incentives harmful to biodiversity, at national level
Keywords: Environment